Phytotoxicity of oil palm residues used as mulch for lettuce, tomato, cucumber and amaranth seedlings - Zamri, Mohd Zakwan (2016)
Wastes of the Malaysian oil palm industry included empty fruit bunch (EFB), palm oil mill effluent (POME), oil palm frond (OPF), chopped trunk (OPT), palm pressed mesocarp fibre (PPMF) and palm kernel shell (PKS), amounting to173.02 million tonnes in 2014. Utilization of these residues is important to maximize uses of resources and overcome environmental pollution. Raw EFB and PPMF have been widely used in oil palm plantation, vegetable farming and landscape industry, as mulching and organic fertilizer. OPT and OPF are produced from old palm and left to rot in the field. Fresh plant wastes could release phytotoxic compounds, affecting growth of other plants. Therefore, the objective of the study were (1) to determine the phytotoxic effect of oil palm wastes, EFB, PPMF, OPF and OPT, using seedling bioassay and seed germination test on four vegetable: lettuce (Lactuca sativa), tomato (Solanum lycopersicum), cucumber (Cucumis sativus) and green amaranth (Amaranthus viridis), and (2) to identify phenolic acid phytotoxic compounds in extracts of selected raw oil palm wastes using thin layer chromatography (TLC). In Experiment 1, oil palm wastes were water extracted to produce aqueous extracts of OPT, EFB, PPMF and OPF. The application OPF aqueous extracts caused greatest radicle length reduction of lettuce, tomato, cucumber and green amaranth seedlings by61.9%, 65%, 53% and 52.6%, respectively, compared with control. PPMF and EFB extracts reduced radicle length significantly compared with OPT extracts, but degree of inhibition on radicle length treated with PPMF was higher than EFB aqueous extracts, with more than 20% radicle reduction for all seedlings, except cucumber seedlings, compared with control. However, OPT aqueous extracts showed no inhibition in radicle growth, hypocotyl growth and fresh and dry weights of all seedlings and total seed germination percentage and mean germination time. Thus, OPT extracts did not release any phytotoxic compounds and it can be concluded that OPF released phytotoxic compounds and degree of inhibition was higher compared with other wastes. PPMF inhibited seedling growth, with greater inhibition compared with EFB and OPT extracts. In Experiment 2, OPF and PPMF were further extracted using four solvents, hexane, diethyl ether, chloroform and ethyl acetate, to determine presence of phytotoxic compounds using seedling bioassay and seed germination test of lettuce, tomato, cucumber and green amaranth. OPF diethyl ether extract exhibited highest inhibition on radicle length of lettuce (48.3%) and tomato (62.6%), but lower for cucumber (27.9%) and green amaranth (26.4%) seedlings. The OPF diethyl ether extract also reduced hypocotyl length of lettuce and green amaranth seedlings significantly compared to control. PPMF diethyl ether extract also reduced radicle length of lettuce, cucumber and green amaranth and hypocotyl length of green amaranth seedlings compared to control. Both solvent extracts showed high inhibition of radicle and hypocotyl length of seedlings compared with other treatments. Phenolic acid compounds present in OPF diethyl ether and PPMF diethyl ether extracts were identified using TLC and compared with 10 phenolic acid standards OPF extracts contained 4-hydroxybenzoic acid and syringic acid, while PPMF diethyl ether extracts contain 4-hydroxybenzaldehyde and syringic acid. OPF and PPMF contained phytotoxic compounds affecting plant growth and their utilization as mulching materials should be avoided to ensure that plants grow without inhibition. However, availability of OPT for mulching is limited since it is only available during oil palm replanting season. Thus, utilization of other readily available and safe oil palm wastes is essential to ensure that seedlings growth is not affected with mulching materials applied. EFB is one of the waste products of oil palm that would be safe to use and easily obtained since it has lower toxicity on seedling growth compared with OPF and PPMF wastes.